Micropolitics and Canadian business : paper, steel, and the airlines - Clancy, Peter, 1949- (CEL - Canadian Publishers Collection., 2004)
Micropolitics and Canadian Business explores the internal structure of industry politics in contemporary Canada. This "micropolitics" approach offers a revealing set of conceptual tools and models that illuminate the politics of everyday business at the industry, firm, and policy issue levels. It builds wider contexts in which the concrete particulars of business-government relations can be explored and understood in a systematic fashion. The approach developed is a comparative one. The book examines three industries-paper, steel, and airlines-carefully chosen to represent a revealing cross-section of a vast economic field covering the primary (resource), secondary (manufacturing), and tertiary (service) sectors of the economy. In addition, one industry (pulp and paper) is primarily export-oriented, another (steel) focuses mainly on domestic sales, and the third (air transport) is strongly grounded in both. The book applies to each a common set of questions and applies a similar set of methods. Separate chapters on each industry begin with a brief review of current industry concerns, followed by a historical and structural survey of that industry. Each chapter continues with studies of two leading firms, highlighting their internal politics and their strategic orientations. Since firms are the building blocks of industry, they tell us much about the larger structures of political power. Finally, each chapter examines two significant public policy controversies whose scope extends beyond core business boundaries. Micropolitics and Canadian Business specifically analyzes three industries; however, the approach used may be applied to a much wider universe of companies and sectors. Throughout, this book furthers our understanding of the complex contexts of business politics. As such, it will be of interest to both students and practitioners of business and government relations